2022
DOI: 10.1371/journal.pone.0269949
|View full text |Cite
|
Sign up to set email alerts
|

Public engagement: Faculty lived experiences and perspectives underscore barriers and a changing culture in academia

Abstract: The idea of faculty engaging in meaningful dialogue with different publics instead of simply communicating their research to interested audiences has gradually morphed from a novel concept to a mainstay within most parts of the academy. Given the wide variety of public engagement modalities, it may be unsurprising that we still lack a comprehensive and granular understanding of factors that influence faculty willingness to engage with public audiences. Those nuances are not always captured by quantitative surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Personas from this study could be used to develop guidelines for supporting scientists of different institutions, career stages, and mediatization patterns to engage in strategic science communication for the benefit of society. For instance, our findings support calls to support faculty members in pursuing meaningful public engagement through changes to review, tenure, and promotion guidelines (e.g., Calice et al, 2022;Alperin et al, 2019]. Our findings could also help communications professionals at institutions and journals adapt their policies and systems to ensure they enable, rather than inhibit, accessible, impactful, and societally beneficial media coverage of research.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Personas from this study could be used to develop guidelines for supporting scientists of different institutions, career stages, and mediatization patterns to engage in strategic science communication for the benefit of society. For instance, our findings support calls to support faculty members in pursuing meaningful public engagement through changes to review, tenure, and promotion guidelines (e.g., Calice et al, 2022;Alperin et al, 2019]. Our findings could also help communications professionals at institutions and journals adapt their policies and systems to ensure they enable, rather than inhibit, accessible, impactful, and societally beneficial media coverage of research.…”
Section: Discussionsupporting
confidence: 73%
“…In developing our personas, scientists' career stage, institutional contexts, and pressures from journals emerged as important forces shaping the nature of their relationships with journalists. This echoes findings by Calice et al [2022] that institutional factors, particularly in regard to tenure and promotion, are crucial in whether or not a scientist will engage with the public. Our study offers a view into how communication professionals at both academic institutions and scholarly journals implicitly and explicitly influence scientists' participation in that competition, with implications for how scientists and journalists work together in the public communication of science.…”
Section: Discussionsupporting
confidence: 66%
“…Additionally, we saw that a large number of our respondents were early-career scientists (Ph.D. candidates and postdoctoral researchers). Previous studies discuss a shift in the culture surrounding more participatory approaches to science communication to be driven by early-career scientists [ 113 ]. However, our findings—although based on a sample in which early career scientists are over-represented—suggest an overall adherence to deficit model approaches, with some elements of dialogue.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings—although based on a sample in which early career scientists are over-represented—suggest an overall adherence to deficit model approaches, with some elements of dialogue. For a discussion on some of the factors (institutional and personal) that may impact the lack of more participatory oriented approaches to science communication, in the context of the United States, see [ 113 , 114 ]. Moreover, while Howell and colleagues [ 115 ] found that both late and early career scientists held positive views on the role of social media in providing opportunities to engage with the public, our respondents’ focus nevertheless remained on deficit-oriented goals when asked about their social media science communication goals.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, where this study is set, the Federal Ministry of Education and Research (BMBF, 2019) has emphasized not only the increasing importance of science communication in general but also the central role of researchers’ public engagement in a policy brief. Although there are studies and surveys on researchers’ general attitudes toward and motivations for science communication and public engagement (e.g., Besley, 2014; Besley et al, 2012; Püttmann et al, 2021; Royal Society, 2006; Valinciute, 2020; Vetenskap & Allmänhet, 2019; Ziegler et al, 2021), less have focused on researchers’ perceptions of their own involvement in science communication, public engagement, and outreach (e.g., Calice et al, 2022; Gantenberg, 2017; Koivumäki & Wilkinson, 2020). Even less studies have considered “the nature and extent of learning from and learning about public dialogue” (Chilvers, 2013, p. 258) for researchers.…”
mentioning
confidence: 99%